Effects of chronic fluoride intake on the antioxidant systems of the liver and kidney in rats - Iano, Flavia Godoy; Ferreira, Maria Cecilia; Quaggio, Giovana Brino [UNESP]; Fernandes, Mileni Silva; Oliveira, Rodrigo Cardoso; Ximenes, Valdecir Farias [UNESP]; Rabelo Buzalaf, Marilia Afonso (Elsevier B.V., 2014)
Excessive fluoride intake over a long period of time can lead to fluorosis, which may cause dental and skeletal manifestations. Metabolic, functional and structural damage caused by chronic fluorosis have been reported in many tissues, but the exact mechanisms modulated by fluoride remain unclear. The aim of this study was to evaluate the effect of fluoride administered in drinking water on the antioxidant defense system of rats. Four groups of Wistar rats were used for the study (n = 10/group). The animals received drinking water containing 0 (control), 5, 15 or 50 mg/L of fluoride over 60 days. They were then euthanized, and their livers and kidneys were collected and homogenized. Superoxide dismutase (SOD), catalase (CAT), glutathione peroxidase (GPx), reduced glutathione (GSH), antioxidants, thiobarbituric acid reactive substances (TBARS), lipid hydroperoxide (LH), and fluoride levels were analyzed. Data were analyzed by ANOVA and Tukey's test or by the Kruskal-Wallis and Dunn's tests (p < 0.05). In the kidneys, the SOD, GPx, GSH and antioxidants levels significantly decreased, while the fluoride and LH levels significantly increased. In the liver, the CAT and TBARS levels significantly decreased, while the fluoride, SOD, LH and antioxidants levels significantly increased. In summary, these results show that chronic fluoride administration alters the antioxidant system of rats. Our data suggest that the conversion of the superoxide anion to water in the kidney upon exposure to high levels of fluoride occurs mainly through SOD and CAT and not through the glutathione system, in contrast to what occurs in the liver.
Keywords: Fluoride; Antioxidants; Oxidative stress; Liver; Kidney